Risk reduction in the new financial architecture: Realities and fallacies in international financial reform - Martin Mayer (Levy Economics Institute of Bard College, 1999)
The causes for the instability that has marked the financial system over the past decade lie deep in the economic theory that urges easy and efficient substitution of one piece of paper for another, in the technology-driven tight articulation of receipts and payments, and in the growth of leverage that diminishes the creditworthiness of major institutions when an interruption in their receipts requires them to seek funds. Many of the proposals aimed at reducing risk in the financial system, however, do not recognize these changes or their importance. The call for greater bank transparency, for example, fails to take into account both that bankers and regulators are jealous of their privacy and that financial markets, not banks, have lately become the more important player in the financial system. Guidelines are needed that reflect the new financial architecture: controls on the creation of leverage in the repo and derivatives markets and limits on banks' freedom to back away from borrowers' cross-border liabilities in currencies other than their own. When such preventive measures fail, then crisis management will require standstill agreements to encourage the continuation of something like normal economic life while the losses from financial failure are sorted out.
Keywords: 330